WAR OF THE ROSES: INTERROGATING THE 1873 PRE-COLONIAL CIVIL WAR IN LAFIA EMIRATES - USMAN, Mohammed Musa (EBSU Journal of Social Sciences and Humanities, 2021)
Towards the end of the third quarter of the 19th Century a momentous events of historical significance took place in Lafia Emirate that change the course of its history, altered the fate and destiny of its people (either for good or bad) and tremendously raise the profile of its historical trajectory. This very event was the climax of a series of other events related or otherwise that preceded it; which also has their root in the discovery, emergence and development of the emirate. The emirate having been founded by people of Kanuri extraction that migrates from Kanem-Bornu at the beginning of the third quarter of the 18th Century in search of a habitable and accommodating environment were led by one Mohammadu Dunama. The paper study the structural defects in the leadership question of the emirate and the inherent contradiction engendered by greed, dominance, insecurity, bad leadership and high-handedness a combination of which made it impossible for harmonious co-existence expected of a pre-colonial African Muslims society. Both contexts are closely related and are mutually re-enforcing. This paper will explore the civil war as it occurs, its remotes and immediate causes. It will also study its far reaching impact on the later development in the Emirate using both thematic and descriptive methods as tools of historical study.